Genetic Markers and Early Diagnosis of Pediatric Autoimmune Diseases: Moving Toward Personalized Therapies - Faiza Mehmood, Mehwish Asghar, Saleha Akram Nizami, Muzamil Liaqat Ali, Muhammad Imran Bajwa, Nida Shafi (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Autoimmune diseases in pediatric populations are marked by heterogeneous onset and progression, making timely diagnosis and individualized treatment pivotal. This study investigates the role of genetic markers